Patient and guardian perspectives on tissue engineering in microtia reconstruction - Arya Sherafat; James Antongiovanni; Chizoba Mosieri; Asthon Rosenbloom; Lana Mamoun; Sierra Willens; Leo Alaniz; Rahim Esfandyarpour; Mary Ziegler; Miles J. Pfaff (PLoS ONE, 2025)
Background Tissue Engineering (TE) is a newer technology with ongoing development across various areas of healthcare. For microtia patients, TE holds promise as a viable option for ear reconstruction, making it essential to understand the perspectives of patients and guardians. This study aimed to evaluate the perspectives of microtia patients and guardians, specifically investigating levels of awareness, comprehension, and interest in TE. Methods A survey and educational material were distributed to microtia patients and guardians. Surveyors were assessed on a Likert scale, and comparative analyses, including two-sample t-testing and multivariate analysis with logistic regression, were used to observe trends in responses. Results A total of 40 surveys were recorded. White patients reported greater familiarity with TE. More than half of the respondents expressed an interest in TE as a reconstructive option. Having a doctor provide TE information positively correlated with willingness to adopt TE reconstruction. Understanding of TE positively correlated with willingness to pursue TE for reconstruction. Patients with more severe grade microtia and white patients were more likely to travel to a hospital that offered TE. Conclusions We found that TE is an unfamiliar concept for most patients. Demographic, socioeconomic, cost, and trust in a doctor played an essential role in patients’ and guardians’ willingness to choose TE for microtia reconstruction. As TE for reconstruction approaches clinical use, these key considerations from a patient and family-centered lens about TE-based reconstruction is critical for application.